2012
DOI: 10.1074/jbc.m112.401620
|View full text |Cite
|
Sign up to set email alerts
|

The First Structure of a Lantibiotic Immunity Protein, SpaI from Bacillus subtilis, Reveals a Novel Fold

Abstract: Background:The periplasmic lipoprotein SpaI protects the subtilin-producing Bacillus subtilis against its own lantibiotic by an unknown mechanism. Results: The first structure of a lantibiotic immunity protein, SpaI, reveals a novel fold and its membrane-interacting regions. Conclusion:The membrane interaction is important for SpaI-mediated immunity. Significance: The SpaI structure will help to understand the immunity of B. subtilis against subtilin on a structural level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 71 publications
2
39
0
1
Order By: Relevance
“…Furthermore, NisI only confers immunity against nisin, whereas SpaI is only active against subtilin and both proteins are not able to confer cross-immunity against the other lantibiotic (24). The structure of SpaI revealed a long, disordered, positively charged N terminus able to interact with membranes and a structured core domain with a central six-stranded ␤-sheet establishing a novel three-dimensional fold class (22). Our solution NMR studies of NisI demonstrate that NisI is a two-domain protein.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Furthermore, NisI only confers immunity against nisin, whereas SpaI is only active against subtilin and both proteins are not able to confer cross-immunity against the other lantibiotic (24). The structure of SpaI revealed a long, disordered, positively charged N terminus able to interact with membranes and a structured core domain with a central six-stranded ␤-sheet establishing a novel three-dimensional fold class (22). Our solution NMR studies of NisI demonstrate that NisI is a two-domain protein.…”
Section: Discussionmentioning
confidence: 88%
“…For SpaI it was shown that the unstructured basic N terminus is able to bind to membranes even in the absence of a lipid anchor (22). NisI does not contain an unstructured N terminus like SpaI but an N-terminal domain with a highly positively charged surface.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations